High iodine adsorption performances under off-gas conditions by bismuth-modified ZnAl-LDH layered double hydroxide. Issue 24 (7th April 2020) - Dinh, Trinh Dinh; Zhang, Dongxiang; Tuan, Vu Ngoc
Abstract : The effective adsorption of radioactive iodine is greatly desirable, but is still a significant challenge. Abstract : The effective adsorption of radioactive iodine is greatly desirable, but is still a significant challenge. In this manuscript, we report the synthesis of a bismuth-modified zinc aluminium layered double hydroxide (BiZnAl-LDH) via a co-precipitation method for the highly efficient absorption of iodine. Based on the robust chemical attraction between Bi and I2, BiZnAl-LDH exhibited highly effective iodine capture. Furthermore, to evaluate BiZnAl-LDH as an effective sorbent, it was characterized via X-ray powder diffraction (XRD), scanning electron microscopy-energy dispersion spectroscopy (SEM-EDS), and Fourier-transform infrared spectroscopy (FITR). In addition, to determine the morphology and iodine adsorption properties of BiZnAl-LDH, several studies were conducted. Through experiments, its elemental composition and vibration before and after iodine adsorption were analyzed via EDS and X-ray photoelectron spectroscopy (XPS). During the capture process, I2 is reduced to I − by the intercalated Bi 3+ via chemical adsorption, and the maximum adsorption capacity of BiZnAl-LDH for iodine reached up to 433 mg g −1, which had a surface area, average pore diameter, and pore volume of 36.259 m 2 g −1, 2.374 nm, and 0.128 m 3 g −1, respectively. Compared with several previous sorbents for iodine adsorption, BiZnAl-LDH exhibited an iodine adsorption of approximately two times that of the commercial Ag-exchange zeolite X, and furthermore BiZnAl-LDH is cost-effective. Thus, the substantial iodine capture by BiZnAl-LDH indicates that it is a capable sorbent for the effective elimination of radioactive iodine from reprocessing plant emissions.